Estudo da função do Fator Transformador de Crescimento (TGF)-ß1 no reparo da polpa dental de camundongos - Reis, Mariana Alvarez Quinta [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The pulp response is limited and the mechanisms involved in this phenomenon are complex, however, not completely understood. The transforming growth factor-beta (TGF-β1) has been reported in several important biological phenomenon to the pulpal as odontogenesis and tissue repair. However, it is unknown yet, the clear role of this growth factor on repair of injured. This study aimed to investigate the profile of pulpal response in the absence of the biological functions of TGF-β1. Balb/c mice were treated with an inhibitor of TGF-β1 receptor (TGFBRI) (SB-431542) or your vehicle only and subjected to induction of direct dentin exposure. After 1, 3, 7 and 15 days, animals were euthanized and specimens were collected and fixed. The mandibles were subjected to histotechnical processing and hematoxylin and eosin (H-E) and Masson Trichrome methods. Morphological analysis was performed by subjective description parameters based on (I) dentin bridge integrity; (II) necrotic areas; (III) presence of inflammatory infiltrate and (IV) fibrosis/hyalinization areas. Additionally, counting the recruitment of neutrophils and mononuclear cells was performed on treated and untreated samples. For immunohistochemical staining was done for protein-1 dentin matrix. Comparative analysis of parameters was made between treated and untreated animals with SB-431542 using the ANOVA test with a Tukey post-test. The results show a little pulpal inflammation, including the migration of neutrophils and vasodilation, as observed in histological postoperative one, three and seven days. Additionally, we can note that the expression of DMP-1 increases with the experimental periods, as observed in the postoperative period of fifteen days, even the inflammation being no longer present. However, the labeling is more intense in the group that inhibited TGF β1, then suggesting that it negatively regulates growth factor-1 DMP-1

A capacidade de reparo da polpa dental é limitada e os mecanismos envolvidos neste fenômeno são complexos, porém, não completamente compreendidos. O fator transformador de crescimento (TGF)β-1 vem sendo relatado em diversos fenômenos importantes para a biologia pulpar como a odontogênese e reparo tecidual. Entretanto, não se sabe até o momento, o papel inequívoco deste fator no reparo da polpa dental lesada. Este estudo teve como objetivo investigar o perfil do reparo pulpar na ausência das funções biológicas de TGF-β1. Camundongos Balb/c foram tratados com um antagonista do receptor de TGF-β1 (TGFBRI) (SB-431542) ou com seu veículo somente e submetidos à indução de exposição dentinária. Após 1, 3, 7 e 15 dias, os animais foram eutanasiados e espécimes foram coletados e fixados. As mandíbulas foram submetidas a processamento histotécnico e coloração por Hematoxilina e Eosina e tricrômio de Masson. A análise morfológica foi realizada por meio de descrição subjetiva com base nos parâmetros (I) integridade da ponte de tecido dentinário; (II) presença de áreas de necrose; (III) presença de infiltrado inflamatório; (IV) áreas de fibrose/hialinização. Adicionalmente, foi realizada a contagem do recrutamento de neutrófilos e células mononucleares nas amostras tratadas e não tratadas. Por meio de imunoistoquímica, foi feita a marcação para a proteína de matriz dentinária-1. A análise comparativa destes parâmetros foi feita entre os animais tratados e não tratados com SB-431542 utilizando o teste ANOVA a um critério com pós-teste de Tukey. Os resultados demonstram um pequeno processo inflamatório na polpa, com a migração de neutrófilos e vasodilatação, como observado nos cortes histológicos de pós-operatório de um, três e sete dias. Além disso, pode-se obervar que a expressão...
Keywords: Polpa dentária; Fator de crescimento transformador beta1; Odontoblastos; Dental pulp